Strength Analysis with Variation of Construction Transverse Watertight Bulkhead On Ship Container 8842 DWT Using Finite Element Method - Amalia Ika Wulandari; Suardi Suardi; Alamsyah Alamsyah; Aknul Ciptiandi (International Journal of Marine Engineering Innovation and Research, 2023)
Abstract - Container ship are commonly employed in a variety of countries, particularly in archipelagic countries like Indonesia. It is a construction that is very important to consider when building a transverse watertight bulkhead ship because it serves as a compartment divider when the ship has a leak and also as a transverse strength of the ship. The purpose of this research is to see if various construction modifications of a transverse watertight bulkhead can bear the working load. The finite element method was employed in this study. Five different constructions of the transverse watertight bulkhead were used in this analysis. The highest stress value in the corrugated watertight bulkhead is 252.44 MPa, with a maximum deformation of 7.6433 mm, whereas the maximum stress value in the transverse plane watertight bulkhead with "angle stiffener" is 330.71 MPa, with a maximum deformation of 12,072 mm. on transverse plane watertight bulkhead with “Tee stiffener” The maximum voltage value of 301.56 MPa and value maximum deformation of 11,025 mm, on transverse plane watertight bulkhead with “bulb stiffener” maximum stress value of 331.98 MPa and value of maximum deformation of 13,421 mm, on transverse plane watertight bulkhead with “flat stiffener” maximum stress value is 484.94 MPa and value of maximum deformation of 16.13mm. According to the safety factor calculation, corrugated watertight bulkheads, transverse plane watertight bulkheads with "Angle stiffener," transverse plane watertight bulkheads with "TEE stiffener," and transverse plane watertight bulkheads with "Bulb stiffener" are all considered safe.